Diversity of praying mantis (Insecta: Mantodea) in Bukit Piton Forest Reserve, Lahad Datu, Sabah - Effa Liyana Norman; Nazirah Mustaffa (Penerbit UMS, 2019)
This study was the first attempt to investigate the praying mantis diversity and composition on a long term basis in a regenerating forest of Bukit Piton Forest Reserve. The study area was a disturbed forest which had been affected by logging activities and forest fires, and undergone a restoration programme. Twelve sampling sessions were carried out over a period of one year, from August 2016 to July 2017, totalling 144 sampling days and nights. Methods included light traps, baited traps, and manual searching. A total of 187 individuals belonging to 19 species were successfully collected. The species sampled represent approximately 16% of the species that occur in Borneo. Mantidae was the dominant family, accounting for about 53% of total species and 36% of total individuals. The dominant species was Tropidomantis tenera which belongs to the family Iridopterygidae and made up 27% of the total individuals. The diversity indices showed that the praying mantis cenosis in the area was moderately diverse. This study highlighted the importance of a regenerating forest for the preservation of a significant portion of the biodiversity. We hope that the information obtained from this study will contribute towards a better understanding of the diversity of this fascinating group of insects, as well as the importance of a regenerating forest as a habitat worthy of conservation efforts.